Transapical off-pump echo-guided mitral valve repair with neochordae implantation mid-term outcomes - Gerosa, Gino; Nadali, Matteo; Longinotti, Lorenzo; Ponzoni, Matteo; Caraffa, Raphael; Fiocco, Alessandro; Pradegan, Nicola; Besola, Laura; D’Onofrio, Augusto; Bizzotto, Eleonora; Bellu, Roberto; Gentian, Denas; et al. (Annals of Cardiothoracic Surgery, 2021)
Background: The NeoChord echo-guided transapical beating heart repair is a promising early-stage minimally invasive surgical procedure for degenerative mitral valve (MV) regurgitation (DMR) correction. The technique has been improved since its inception following procedure standardization, patient selection optimization, and learning curve stabilization. We hereby present the mid-term clinical results through three years of our large single center experience. Methods: All consecutive patients with severe symptomatic DMR due to prolapse or flail of one or both mitral leaflets that underwent the NeoChord procedure between November 2013 and June 2019 were included. Patients were categorized according to MV anatomy; Type A isolated central posterior leaflet prolapse and/or flail, Type B posterior multi-segment prolapse and/or flail, Type C anterior and/or bi-leaflet prolapse or flail, Type D paracommissural prolapse and/or flail and/or significant leaflet and/or annular calcifications. Patients underwent clinical and echocardiographic follow-up at one, three, six, twelve months and yearly thereafter. Clinical outcomes and the composite primary endpoint (patient success) were defined according to Mitral Valve Academic Research Consortium (MVARC) criteria. Mitral regurgitation (MR) severity was graded as absent, mild, moderate and severe according to American Society of Echocardiography (ASE) and European Society of Cardiology (ESC) guidelines. Results: Two hundred and three patients were included; median follow-up was 24 months [interquartile range (IQR), 9–36]. Median age was 64 years (IQR, 54–74 years), median Society of Thoracic Surgeons (STS) Predicted Risk of Mortality (PROM) was 0.60% (IQR, 0.32–1.44%). There were 106 Type A patients (52.2%), 68 Type B (33.5%), 16 Type C (7.9%), and 13 Type D (6.4%). Kaplan-Meier estimate of survival was 99.0%±0.7% at one and two years and 94.0%±2.9% at three years. At one-year follow-up patient success was 91.2%±2.0% and 111 patients (74%) presented a residual MR mild or less (1+). At three-year follow-up patient success was 81.2%±3.8% and 32 patients (64%) had a residual MR mild or less (1+). Patient success was significantly different according to anatomical type (P=0.001). Echocardiographic analysis showed a significant acute left ventricle and left atrial reverse remodeling that was maintained up to three years. Conclusions: The NeoChord echo-guided transapical beating heart repair procedure demonstrated good clinical outcomes and echocardiographic results up to three-year follow-up.